The thematic organization of information resources in libraries: a brief diachronic analysis from antiquity to the present day - Suárez Sánchez, Adriana (2021)
The subject organization of informational resources in libraries has been an essential activity since the ancient civilizations to our present day. The target of this work is to present a diachronic revision of the subject organization taking into consideration the resources, the processes, the people who develop them, and the indexing languages employed in such activities. The methodology for this work consists in the revision and analysis of a set of academic sources of information on the topic. This work proves that the subject organization of informational resources has undergone different phases that can be categorized into four different periods: (1) before the establishment of librarianship as a discipline, (2) the stage under the library codes and standards in the nineteenth and twenty centuries, (3) during the second half of the twenty century and (4) the starting of the 21st century. Conclusively, this is an activity that has evolved, constantly, as the informational resources, the technologies employed for their classification, and the needs of their users have required it.